2009
DOI: 10.1016/j.brainres.2009.02.017
|View full text |Cite
|
Sign up to set email alerts
|

The role of glucocorticoids for spiral ganglion neuron survival

Abstract: Glucocorticoids, which are steroidal stress hormones, have a broad array of biological functions. Synthetic glucocorticoids are frequently used therapeutically for many pathologic conditions, including diseases of the inner ear. Despite their use, their exact functions in the cochlea are not completely understood. Recent work has clearly demonstrated the presence of glucocorticoid signaling pathways in the cochlea and their protective roles against noise-induced hearing loss. Furthermore, indirect evidence sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 110 publications
0
18
0
Order By: Relevance
“…High doses of MDMA also cause neurotoxicity through increased glutamate levels (Sarkar & Schmued, 2010), oxidative stress (Fiaschi & Cerretani, 2010; Sarkar & Schmued, 2010), and ischemia/vasoconstriction (Baker et al, 2007; Bingham et al, 1998). Similarly, NIHL is associated with neural toxicity from reduced adenosine levels (Vlajkovic et al, 2009), reduced nicotinic acetylcholinergic activity (Elgoyhen et al, 2009), reduced glucocorticoid receptor activity (Jin et al, 2009), increased glutamate release (Le Prell et al, 2007), oxidative stress (Le Prell et al, 2007), ischemia in the stria vascularis (Le Prell et al, 2007), and serotonin and dopamine depletion (Lendvai et al, 2011; Papesh & Hurley, 2012; Tong et al, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…High doses of MDMA also cause neurotoxicity through increased glutamate levels (Sarkar & Schmued, 2010), oxidative stress (Fiaschi & Cerretani, 2010; Sarkar & Schmued, 2010), and ischemia/vasoconstriction (Baker et al, 2007; Bingham et al, 1998). Similarly, NIHL is associated with neural toxicity from reduced adenosine levels (Vlajkovic et al, 2009), reduced nicotinic acetylcholinergic activity (Elgoyhen et al, 2009), reduced glucocorticoid receptor activity (Jin et al, 2009), increased glutamate release (Le Prell et al, 2007), oxidative stress (Le Prell et al, 2007), ischemia in the stria vascularis (Le Prell et al, 2007), and serotonin and dopamine depletion (Lendvai et al, 2011; Papesh & Hurley, 2012; Tong et al, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…It was manifested that high concentration of glucocorticoids (GC) can change the biological properties of neurons' plasma membrane, which results in impaired ions movement cycle across the cell membrane and deficiencies of nerve impulse transmission (22). Given that rats exposed to prenatal stress have a higher level of basic GC (5), there is a possibility that their neuronal function is impaired and thus the action potential transmission time is increased (22). Previous research has also reported the malfunction of different parts of the central nervous system (CNS) in animals exposed to prenatal stress (22).…”
Section: Discussionmentioning
confidence: 99%
“…Given that rats exposed to prenatal stress have a higher level of basic GC (5), there is a possibility that their neuronal function is impaired and thus the action potential transmission time is increased (22). Previous research has also reported the malfunction of different parts of the central nervous system (CNS) in animals exposed to prenatal stress (22). During the aging process, similar to prenatal stress exposure, malfunction of HPA axis and rising the basic level of GC in blood can occur (23).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of GCs to reduce NIHL has been demonstrated in various animal models (for recent reviews see Jin et al, 2009; Trune and Canlon, 2012). However, GCs are known to cause serious dose-dependent side effects, including psychosis, gastritis, hypertension, insulin resistance, sleep disturbances, and aseptic necrosis of the hip (Hanaoka et al, 2012).…”
Section: Discussionmentioning
confidence: 99%